Validation of a Spanish version of the Leicester Cough Questionnaire in cystic fibrosis. (16th August 2021) - Muñoz, Gerard; de Gracia, Javier; Giron, Rosa; Olveira, Casilda; Alvarez, Antonio; Buxó, Maria; Birring, Surinder S; Vendrell, Montserrat
Cough is a main symptom in cystic fibrosis (CF). We aim to validate a Spanish version of the Leicester Cough Questionnaire (LCQ-Sp) to measure the impact of cough in CF bronchiectasis. A prospective longitudinal multicentre study was performed. Internal consistency and score changes over a 15-day period in stable state were assessed to analyse reliability. Concurrent validity was analysed by correlation with Saint George's Respiratory Questionnaire (SGRQ) and convergent validity by assessing the association with clinical variables. Changes in scores between stable state and the first exacerbation were assessed to analyse responsiveness. 132 patients (29.73 ± 10.52 years) were enrolled in four hospitals. Internal consistency was high for the total score and good for the three domains (Cronbach's α 0.81–0.93). The test–retest reliability showed an intraclass correlation coefficient of 0.86 for the total score. The correlation between LCQ-Sp and SGRQ scores was −0.74. The LCQ-Sp score negatively correlated with sputum volume, and the mean score decreased at the beginning of exacerbations (16.04±3.81 vs 13.91±4.29) with a large effect size. The LCQ-Sp is a reliable, repeatable and responsive instrument to assess the impact of cough in CF bronchiectasis and is responsive to change in the event of exacerbations.